Optical glass, glass preforms, optical components and optical instruments
By rationally designing the components of optical glass, reducing the Li2O content, controlling the refractive index and Abbe number, the existing low-melting point glass has been solved, and the low-cost and high-stability optical glass suitable for aspherical lenses is achieved.
Patent Information
- Application Number
- CN202311137421.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-05
AI Technical Summary
The existing low-melting point glass has high cost and poor chemical stability in the manufacture of aspherical lenses, making it difficult to meet the needs of high definition, miniaturization and lightweight.
By rationally designing the components of optical glass, the Li2O content is reduced, and oxides such as SiO2, B2O3, Al2O3, Na2O, K2O, ZnO are used as main components, and the refractive index is controlled between 1.49 and 1.55 and the Abbe number is between 58 and 68.
It realizes optical glass with low cost and high chemical stability, and is suitable for precision molding technology, meeting the high definition, miniaturization and lightweight needs of aspherical lenses.
Smart Images

Figure BDA0004432303140000071 
Figure BDA0004432303140000101 
Figure BDA0004432303140000111
Abstract
Description
Technical Field
[0001] The invention relates to an optical glass, in particular to an optical glass with a refractive index of 1.49-1.55 and an Abbe number of 58-68, and a glass preform, an optical element and an optical instrument made of the optical glass. Background Art
[0002] With the rapid development of artificial intelligence technologies such as smart driving, medical health monitoring, smart surveillance, and face recognition, higher requirements are placed on the high definition, miniaturization, and lightweight of optical components. These optical components need to be realized through aspherical lenses, so the application of aspherical lenses is becoming more and more extensive.
[0003] At present, the mainstream technology for manufacturing aspherical lenses is precision molding technology, which requires the use of low-melting-point glass. Low-melting-point glass in existing technologies uses more Li2O to reduce the transition temperature. However, the high price of Li2O in recent years has made the cost of this type of glass high. At the same time, more Li2O greatly reduces the chemical stability of the glass, resulting in limited use of the glass. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an optical glass with low cost, a refractive index of 1.49-1.55 and an Abbe number of 58-68.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] (1) Optical glass, the components of which, expressed in percentage by weight, contain: SiO2: 50-80%; B2O3: 5-20%; Al2O3: greater than 0.5% but less than 10%; Li2O: greater than 0.5% but less than 5%; Na2O: 1-15%; K2O: 1-10%; ZnO: 0.05-10%.
[0007] (2) The optical glass according to (1), wherein the components, expressed in weight percentage, further contain: TiO2: 0-5%; and / or Nb2O5: 0-5%; and / or WO3: 0-5%; and / or BaO: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or Sb2O3: 0-1%.
[0008] (3) Optical glass, the components of which are expressed in weight percentage and consist of SiO2: 50-80%; B2O3: 5-20%; Al2O3: greater than 0.5% but less than 10%; Li2O: greater than 0.5% but less than 5%; Na2O: 1-15%; K2O: 1-10%; ZnO: 0.05-10%; TiO2: 0-5%; Nb2O5: 0-5%; WO3: 0-5%; BaO: 0-5%; MgO: 0-5%; CaO: 0-5%; SrO: 0-5%; Sb2O3: 0-1%.
[0009] (4) The optical glass according to any one of (1) to (3), wherein the components, expressed in weight percentage, include: SiO2: 55-75%, preferably SiO2: 60-70%; and / or B2O3: 7-18%, preferably B2O3: 8-15%; and / or Al2O3: 1-8%, preferably Al2O3: 1-7%; and / or Li2O: 0.7-4%, preferably Li2O: 1-4%; and / or Na2O: 5-13%, preferably Na2O: 8 ~12%; and / or K2O: 2~8%, preferably K2O: 2~7%; and / or ZnO: 0.5~8%, preferably ZnO: 0.5~5%; and / or TiO2: 0.05~3%; and / or Nb2O5: 0.05~3%; and / or WO3: 0~3%; and / or BaO: 0~3%; and / or MgO: 0~3%; and / or CaO: 0~3%; and / or SrO: 0~3%; and / or Sb2O3: 0.05~0.5%.
[0010] (5) The optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: TiO2 / (Al2O3+ZnO+Li2O) is less than 0.20, preferably TiO2 / (Al2O3+ZnO+Li2O) is less than 0.15; and / or Nb2O5 / (Al2O3+ZnO+Li2O) is less than 0.20, preferably Nb2O5 / (Al2O3+ZnO+Li2O) is less than 0.15; and / or (ZnO+Li2O) / K2O is 0.70 to 3.00, preferably Selected as 0.90~2.50, more preferably 0.90~2.00; and / or Li2O / (Al2O3+ZnO+Li2O) is 0.10~1.50, preferably 0.15~1.00, more preferably 0.15~0.90; and / or Al2O3 / SiO2 is 0.01~0.15, preferably 0.01~0.1, more preferably 0.01~0.08; and / or K2O / B2O3 is 0.05~1.00, preferably 0.10~0.80, more preferably 0.10~0.50.
[0011] (6) An optical glass according to any one of (1) to (2), characterized in that its components do not contain ZrO2; and / or do not contain La2O3; and / or do not contain Y2O3; and / or do not contain Gd2O3; and / or do not contain WO3; and / or do not contain F; and / or do not contain TiO2; and / or do not contain Nb2O5.
[0012] (7) The optical glass according to any one of (1) to (4), wherein the refractive index n d is 1.49 to 1.55, preferably 1.50 to 1.53, more preferably 1.51 to 1.53; Abbe number v d It is 58-68, preferably 60-66, and more preferably 62-65.
[0013] (8) The optical glass according to any one of (1) to (4), wherein the transition temperature of the optical glass is g is below 570°C, preferably below 560°C, more preferably below 550°C; and / or the acid resistance stability DA is above Class 2, preferably above Class 1; and / or the weather resistance stability CR is above Class 2, preferably above Class 1; and / or the wavelength λ corresponding to the transmittance reaching 80% 80 Below 350nm; and / or the corresponding wavelength λ5 when the transmittance reaches 5% is below 310nm; and / or the thermal expansion coefficient α 100 / 300℃ 90×10 -7 / K or less, preferably 85×10 -7 / K or less; and / or density ρ is 2.60g / cm 3 Below, preferably 2.55g / cm 3 and / or the bubble degree is above grade A, preferably above grade A0, more preferably A 00 class.
[0014] (9) A glass preform made of the optical glass described in any one of (1) to (8).
[0015] (10) An optical element, made of the optical glass described in any one of (1) to (8), or made of the glass preform described in (9).
[0016] (11) An optical instrument comprising the optical glass described in any one of (1) to (8), or the optical element described in (10).
[0017] The beneficial effects of the present invention are as follows: the present invention reduces the content of Li2O through reasonable component design, thereby obtaining a low-cost optical glass suitable for precision molding with a refractive index of 1.49-1.55 and an Abbe number of 58-68. DETAILED DESCRIPTION
[0018] The following describes the embodiments of the present invention in detail, but the present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention is not limited thereto. In the following content, the optical glass of the present invention is sometimes referred to as glass.
[0019] [Optical glass]
[0020] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0021] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include the endpoints, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0022] <Essential Components and Optional Components>
[0023] SiO2 is the network generator of the optical glass of the present invention, which constitutes the skeleton of the glass and can ensure the excellent chemical stability of the glass and the stability of the glass properties. When the SiO2 content is lower than 50%, it is difficult to form the glass and the above-mentioned effect cannot be achieved; but when the SiO2 content is higher than 80%, the glass is extremely difficult to melt and it is difficult to obtain the refractive index required by the present invention. Therefore, the content of SiO2 is 50-80%, preferably 55-75%, and more preferably 60-70%.
[0024] B2O3 is also a network generator of the glass of the present invention, and also has the function of fluxing and improving the glass-forming ability. In the present invention, more than 5% of B2O3 is introduced to improve the glass-forming performance, which plays a role of fluxing; but when the B2O3 content is greater than 20%, the chemical stability of the glass deteriorates, the volatilization of B2O3 increases, the refractive index and Abbe number of the glass fluctuate greatly, and the stability of the above data cannot be guaranteed. Therefore, the B2O3 content is limited to 5-20%, preferably 7-18%, and more preferably 8-15%.
[0025] Al2O3 can improve the chemical stability of glass and ensure a low thermal expansion coefficient, but when its content is above 10%, the melting ability of glass is very poor. Therefore, the content of Al2O3 in the present invention is greater than 0.5% but less than 10%, preferably 1-8%, and more preferably 1-7%.
[0026] In some embodiments, by making Al2O3 / SiO2 in the range of 0.01 to 0.15, the glass has excellent chemical stability, can ensure its melting performance, reduce the stone inside the glass, and thus ensure a good bubble level. Therefore, in the present invention, the value of Al2O3 / SiO2 is 0.01 to 0.15, preferably 0.01 to 0.1, and more preferably 0.01 to 0.08.
[0027] Li2O can lower the melting temperature of glass and is a good fluxing component. In the present invention, the above effect is achieved by introducing more than 0.5% Li2O. Preferably, the Li2O content is more than 0.7%, and more preferably, more than 1%. However, when the Li2O content increases, the thermal expansion coefficient of the glass increases, the mechanical processing ability deteriorates, and the chemical stability also deteriorates. Therefore, the Li2O content is less than 5%, and preferably the Li2O content is less than 4%.
[0028] Na2O can lower the glass transition temperature and has a significant effect on lowering the melting temperature and improving the glass solubility. In the present invention, more than 1% of Na2O is introduced to obtain the above-mentioned effect. Preferably, the Na2O content is more than 5%, and more preferably more than 8%. When the Na2O content exceeds 15%, the chemical stability and weather resistance of the glass are significantly reduced. Therefore, the Na2O content is less than 15%, preferably less than 13%, and more preferably less than 12%.
[0029] K2O has a good fluxing effect and can reduce the glass transition temperature. When its content exceeds 10%, the anti-crystallization performance of the glass is significantly reduced and the chemical stability of the glass becomes worse. Therefore, the K2O content is 1-10%, preferably 2-8%, and more preferably 2-7%.
[0030] In some embodiments, if K2O / B2O3 is lower than 0.05, the melting performance of the glass is poor and the melting temperature is high; if K2O / B2O3 is higher than 1.00, the crystallization performance of the glass deteriorates and stable glass cannot be obtained. Therefore, the range of K2O / B2O3 is 0.05-1.00, preferably 0.10-0.80, and more preferably 0.10-0.50.
[0031] An appropriate amount of ZnO can reduce the transition temperature of glass and improve the chemical stability and weather resistance of glass. When its content exceeds 10%, the transmittance and chemical stability of glass are significantly reduced. Therefore, the content of ZnO is 0.05-10%, preferably 0.5-8%, and more preferably 0.5-5%.
[0032] In some embodiments, by making (ZnO+Li2O) / K2O in the range of 0.70 to 3.00, it can be ensured that the glass of the present invention has a low transition temperature, stable glass properties, strong resistance to devitrification, excellent chemical stability and weather resistance, and can also ensure excellent melting properties of the glass. Preferably, (ZnO+Li2O) / K2O is 0.90 to 2.50, and more preferably 0.90 to 2.00.
[0033] In some embodiments, by making Li2O / (Al2O3+ZnO+Li2O) in the range of 0.10 to 1.50, the glass can have low cost while ensuring that the glass has a low transition temperature. Preferably, Li2O / (Al2O3+ZnO+Li2O) is 0.15 to 1.00, and more preferably 0.15 to 0.90.
[0034] TiO2 can significantly increase the refractive index and dispersion of glass and improve the chemical stability of glass. In the present invention, the content of TiO2 is 0-5%, preferably 0.05-3%. In some embodiments of the present invention, it is preferred not to introduce TiO2.
[0035] In some embodiments, the value of TiO2 / (Al2O3+ZnO+Li2O) is controlled to be less than 0.20, so that the glass has a low coloring degree λ while ensuring that the glass obtains the target refractive index and dispersion. 80 / λ5, preferably TiO2 / (Al2O3+ZnO+Li2O) is less than 0.15.
[0036] Nb2O5 can improve the refractive index and dispersion of glass. The content of Nb2O5 is limited to 0-5%, preferably 0.05-3%. In some embodiments of the present invention, it is preferred not to introduce Nb2O5.
[0037] In some embodiments, the value of Nb2O5 / (Al2O3+ZnO+Li2O) is controlled to be less than 0.20. This can ensure that the glass obtains the target optical constants without reducing the transmittance of the glass. Preferably, Nb2O5 / (Al2O3+ZnO+Li2O) is less than 0.15.
[0038] WO3 can improve the refractive index, but when its content exceeds 5%, the transmittance of the glass drops sharply. Therefore, the content of WO3 in the present invention is 0 to 5%, preferably 0 to 3%, and more preferably no WO3 is contained.
[0039] BaO can adjust the refractive index of glass and increase the stability of the glass system, but adding too much will deteriorate the chemical stability of the glass and increase the density of the glass. Therefore, the BaO content is limited to 0-5%, preferably 0-3%.
[0040] CaO helps to adjust the optical constants of glass and increase the mechanical strength of glass, but when too much CaO is added, the anti-crystallization performance of glass deteriorates. Therefore, the CaO content is limited to 0-5%, preferably 0-3%.
[0041] SrO can increase the refractive index and Abbe number of glass, but if added in excess, the chemical stability of the glass decreases. Therefore, the SrO content is limited to 0-5%, preferably 0-3%.
[0042] MgO is used to adjust the optical constants, but if MgO is added in excess, the glass-forming stability of the glass decreases. Therefore, the MgO content is limited to 0-5%, preferably 0-3%.
[0043] Sb2O3 is a glass clarifier. Adding a small amount of Sb2O3 is beneficial to clarifying the glass and eliminating bubbles inside the glass. However, when the Sb2O3 content exceeds 1%, it will be detrimental to the clarification of the glass. Therefore, the Sb2O3 content in the present invention is limited to 0-1%, preferably 0.05-0.5%.
[0044] <Components that should not be contained>
[0045] The components ZrO2, La2O3, Y2O3, and Gd2O3 are refractory substances, which can cause stones to form inside the glass, seriously affecting the bubble level of the product; at the same time, these components will also cause the glass transition temperature of the present invention to increase, and low-melting point glass cannot be obtained. Therefore, the present invention does not contain the components ZrO2, La2O3, Y2O3, and Gd2O3.
[0046] F is a very volatile component, which will cause large fluctuations in the refractive index and Abbe number of the glass, and will also reduce the high-temperature viscosity of the glass. It is easy to crystallize and generate stripes during glass molding. Therefore, the present invention does not contain F.
[0047] In order to achieve environmental friendliness, the glass of the present invention does not contain As2O3 and PbO.
[0048] The "not introduced", "not containing" and "0%" recorded in this article mean that the compound, molecule or element will not be actively added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing glass, there will be certain impurities or components that are not intentionally added and will be contained in a small amount in the final glass. This situation is also within the scope of protection of the patent of this invention.
[0049] Next, the properties of the optical glass of the present invention will be described.
[0050] <Refractive Index and Abbe Number>
[0051] The refractive index of glass (n d ) and the Abbe number (νd ) Tested according to the method specified in GB / T 7962.1-2010.
[0052] The refractive index of the glass of the present invention (n d ) is 1.49 to 1.55, preferably 1.50 to 1.53, more preferably 1.51 to 1.53; Abbe number (v d ) is 58-68, preferably 60-66, and more preferably 62-65.
[0053] <Acid resistance stability>
[0054] The acid resistance stability (DA) (powder method) of glass is tested according to the method specified in GB / T17129.
[0055] The acid resistance stability (DA) (powder method) of the glass of the present invention is Class 2 or higher, preferably Class 1.
[0056] <Weather resistance>
[0057] The weather resistance (CR) of optical glass is tested according to the following method.
[0058] The samples were placed in a test box with a saturated water vapor environment of 90% relative humidity, and cycled alternately every 1 hour at 40-50°C for 15 cycles. The weather resistance category was divided according to the change in turbidity before and after the samples were placed. Table 1 shows the weather resistance classification.
[0059] Table 1. Weather resistance classification
[0060]
[0061] The weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.
[0062] <Bubble Degree>
[0063] The bubble degree of glass is tested according to the method specified in GB / T7962.8-2010.
[0064] The bubble degree of the glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A. 00 class.
[0065] <Transition Temperature>
[0066] The glass transition temperature (T g ) Tested according to the method specified in GB / T7962.16-2010.
[0067] The transition temperature (T g ) is 570°C or lower, preferably 560°C or lower, and more preferably 550°C or lower.
[0068] <Coefficient of Thermal Expansion>
[0069] Thermal expansion coefficient of glass (α 100 / 300℃ ) The data of 100~300℃ were tested according to the method specified in GB / T7962.16-2010.
[0070] The thermal expansion coefficient α of the optical glass of the present invention is 100 / 300℃ 90×10 -7 / K or less, preferably 85×10 -7 / K or less.
[0071] <Color of glass>
[0072] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 80 / λ5). 80 It refers to the wavelength when the glass transmittance reaches 80%, and λ5 refers to the wavelength when the glass transmittance reaches 5%. 80 The measurement is to use a glass with a thickness of 10±0.1mm having two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength showing a transmittance of 80%. The spectral transmittance or transmittance is the amount represented by Iout / Iin when light with an intensity of Iin is incident perpendicularly to the above surface of the glass, passes through the glass and emits light with an intensity of Iout from one plane, and also includes the transmittance of the surface reflection loss on the above surface of the glass.
[0073] The optical glass of the present invention 80 Below 350nm, λ5 is below 310nm.
[0074] <density>
[0075] The density of optical glass is the mass per unit volume at a temperature of 20°C. The density of optical glass is measured according to the method specified in GB / T7962.20-2010 and is expressed in g / cm 3 express.
[0076] The density of the optical glass of the present invention is 2.60 g / cm 3 Below, preferably 2.55g / cm 3 the following.
[0077] [Manufacturing method of glass]
[0078] The manufacturing method of the glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and conventional processes, using oxides, carbonates, nitrates, hydroxides, etc. as raw materials, and after mixing according to conventional methods, the mixed furnace materials are put into a melting furnace at 1200-1400° C. for melting, and after clarification, stirring and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0079] [Glass preforms and optical components]
[0080] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0081] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of the glass of the present invention; the optical element of the present invention has the excellent properties of the glass of the present invention, and can provide various optical elements such as lenses and prisms with high optical value.
[0082] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0083] [Optical instruments]
[0084] The optical glass of the present invention or the optical element formed by the optical glass can be used to manufacture optical instruments such as photographic equipment, video equipment, display equipment, monitoring equipment and vehicle-mounted equipment.
[0085] Example
[0086] <Optical Glass Example>
[0087] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided.
[0088] In Examples 1 to 30, the above-mentioned glass manufacturing method was used to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass were measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.
[0089] Table 2
[0090]
[0091]
[0092] Table 3
[0093]
[0094]
[0095] Table 4
[0096]
[0097]
[0098] <Glass Preform Example>
[0099] The glass optical glass obtained from glass embodiments 1 to 30 is cut into predetermined sizes, and then a release agent is evenly coated on the surface. It is then heated, softened, and press-formed to produce preforms of various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, double convex lenses, double concave lenses, plano-convex lenses, and plano-concave lenses.
[0100] <Optical Element Embodiment>
[0101] The preforms obtained from the above optical preform embodiments are annealed so that the optical properties such as the refractive index reach the desired values.
[0102] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0103] <Optical Instrument Embodiment>
[0104] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements. It can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips, or in camera equipment and devices in the vehicle field.
Claims
1. Optical glass, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 50-80%; B2O3: 5-20%; Al2O3: greater than 0.5% but less than 10%; Li2O: greater than or equal to 2.08% but less than 5%; Na2O: 1-15%; K2O: 1-10%; ZnO: 0.05-10%, (ZnO+Li2O) / K2O is 1.5-2.25, Li2O / (Al2O3+ZnO+Li2O) is 0.10-1.50, and does not contain TiO2.
2. The optical glass according to claim 1, wherein: Its components, expressed in weight percentage, also contain: Nb2O5: 0-5%; and / or WO3: 0-5%; and / or BaO: 0-5%; and / or MgO: 0-5%; and / or CaO: 0-5%; and / or SrO: 0-5%; and / or Sb2O3: 0-1%.
3. Optical glass, characterized in that: Its components are expressed in weight percentage, SiO2: 50-80%; B2O3: 5-20%; Al2O3: greater than 0.5% but less than 10%; Li2O: greater than or equal to 2.08% but less than 5%; Na2O: 1-15%; K2O: 1-10%; ZnO: 0.05-10%; Nb2O5: 0-5%; WO3: 0-5%; BaO: 0-5%; MgO: 0-5%; CaO: 0-5%; SrO: 0~5%; Sb2O3: 0~1%, (ZnO+Li2O) / K2O is 1.5~2.25, Li2O / (Al2O3+ZnO+Li2O) is 0.10~1.
50.
4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 55-75%; and / or B2O3: 7-18%; and / or Al2O3: 1-8%; and / or Li2O: greater than or equal to 2.08% but less than 4%; and / or Na2O: 5-13%; and / or K2O: 2-8%; and / or ZnO: 0.5-8%; and / or Nb2O5: 0.05-3%; and / or WO3: 0-3%; and / or BaO: 0-3%; and / or MgO: 0-3%; and / or CaO: 0-3%; and / or SrO: 0-3%; and / or Sb2O3: 0.05-0.5%.
5. The optical glass according to any one of claims 1 to 3, characterized in that: Its components, expressed in weight percentage, include: SiO2: 60-70%; and / or B2O3: 8-15%; and / or Al2O3: 1-7%; and / or Li2O: greater than or equal to 2.08% but less than or equal to 4%; and / or Na2O: 8-12%; and / or K2O: 2-7%; and / or ZnO: 0.5-5%.
6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: Nb2O5 / (Al2O3+ZnO+Li2O) is less than 0.20; and / or (ZnO+Li2O) / K2O is 1.5-2.00; and / or Al2O3 / SiO2 is 0.01-0.15; and / or K2O / B2O3 is 0.05-1.
00.
7. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: Nb2O5 / (Al2O3+ZnO+Li2O) is less than 0.15; and / or Li2O / (Al2O3+ZnO+Li2O) is 0.15-1.00; and / or Al2O3 / SiO2 is 0.01-0.1; and / or K2O / B2O3 is 0.10-0.
80.
8. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: Li2O / (Al2O3+ZnO+Li2O) is 0.15-0.90; and / or Al2O3 / SiO2 is 0.01-0.08; and / or K2O / B2O3 is 0.10-0.
50.
9. The optical glass according to any one of claims 1 to 2, characterized in that: Its components do not contain ZrO2; and / or do not contain La2O3; and / or do not contain Y2O3; and / or do not contain Gd2O3; and / or do not contain WO3; and / or do not contain F; and / or do not contain Nb2O5.
10. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d 1.49~1.55; Abbe number v d It is 58 to 68.
11. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d 1.50~1.53; Abbe number v d It is 60 to 66.
12. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d is 1.51~1.53; Abbe number v d It is 62-65.
13. The optical glass according to any one of claims 1 to 3, characterized in that: The transition temperature T of the optical glass g 570℃ or less; and / or acid resistance stability DA is 2 or more; and / or weather resistance stability CR is 2 or more; and / or the wavelength λ corresponding to the transmittance reaching 80% 80 Below 350nm; and / or the corresponding wavelength λ5 when the transmittance reaches 5% is below 310nm; and / or the thermal expansion coefficient α 100 / 300℃ 90×10 -7 / K or less; and / or density ρ is 2.60g / cm 3 and / or the bubble degree is above grade A.
14. The optical glass according to any one of claims 1 to 3, characterized in that: The transition temperature T of the optical glass g 560°C or less; and / or acid resistance stability DA is Class 1 or above; and / or weather resistance stability CR is Class 1 or above; and / or thermal expansion coefficient α 100 / 300℃ 85×10 -7 / K or less; and / or density ρ is 2.55g / cm 3 Below; and / or the bubble degree is above A0 level.
15. The optical glass according to any one of claims 1 to 3, characterized in that: The transition temperature T of the optical glass g Below 550℃; and / or bubble degree is A 00 class.
16. A glass preform made of the optical glass according to any one of claims 1 to 15.
17. An optical element, made of the optical glass according to any one of claims 1 to 15, or made of the glass preform according to claim 16.
18. An optical instrument comprising the optical glass according to any one of claims 1 to 15, or the optical element according to claim 17.
Citation Information
Patent Citations
Borosilicate optical glass and an optical element
CN105585245A
Optical glass, glass preform, optical element and optical instrument
CN113754278A